Lentiviral-Mediated Beclin-1 Overexpression Inhibits Cell Proliferation and Induces Autophagy of Human Esophageal Carcinoma Eca109 Cell Xenograft in Nude Mice - Zhang, Junhe; Dong, Weihua (Recent Patents on Anti-Cancer Drug Discovery, 2020)
Background: Esophageal carcinoma is one of the common malignant tumors in digestive tract. BECLIN-1 is a key gene that regulates autophagy, and its abnormal expression may be related with many human tumors. However, the mechanism of BECLIN-1 in esophageal carcinoma remains unknown. Objective: In this study, we explored the effect of BECLIN-1 overexpression on tumor growth in mice with esophageal carcinoma and its mechanism. Methods: Recombined lentiviral vector containing BECLIN-1 was used to transfect human esophageal carcinoma Eca109 cells and establish stable cell line. qRT-PCR was used to detect BECLIN-1 mRNA level in the transfected Eca109 cells, CCK-8 assay was used to detect cell proliferation. Beclin-1, P62 and LC3-II protein expression levels in Eca109 cells were detected using Western blot analysis. Subcutaneous xenograft nude mice model of human esophageal carcinoma was established, and the tumor growths in Beclin-1 group, control group and empty vector group were monitored. Beclin-1 protein expression in vivo was detected by immunohistochemistry. Results: Beclin-1 mRNA and protein were overexpressed in Eca109 cells. Compared with empty vector group, the growth rate of cells transfected with BECLIN-1 decreased significantly. Compared with the control group and empty vector group, the expression level of P62 protein in beclin-1 group was significantly decreased, while the expression level of LC3-II protein was significantly increased. The tumor growth rate in nude mice of Beclin-1 group was significantly lower than that of the control group and empty vector group, and Beclin-1 protein was mainly expressed in Beclin-1 group in vivo. Conclusion: BECLIN-1 can induce autophagy in esophageal carcinoma Eca109 cells, and it can significantly inhibit the growth of esophageal carcinoma.
Keywords: tumor growth